2015
DOI: 10.2528/pierc15012001
|View full text |Cite
|
Sign up to set email alerts
|

Design of a 225 GHZ High Output Power Tripler Based on Unbalanced Structure

Abstract: Abstract-We report the results of a high-output power unbalanced tripler at 225 GHz, in which a pair of discrete Schottky varactor chips in parallel is adopted. Considering the present situation of domestic processing technology, the advantage of unbalanced structure is that it could provide bias to the diodes without a on-chip capacitor, which is essential in the balanced tripler scheme. The whole circuits are built on a 50 µm-thick quartz substrate, and the novel field-circuit method is applied to the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In consideration of thermal dissipation, it is necessary to design a tripler with high efficiency to reduce requirement for high output power of the former source. In fact, the tripler based on unbalanced structure has been studied in our former research work, and the measured results show that the highest efficiency is 7.3% [8]. Compared with it, the performance of the 212 GHz tripler designed in this paper improves greatly.…”
Section: Ghz Triplermentioning
confidence: 68%
“…In consideration of thermal dissipation, it is necessary to design a tripler with high efficiency to reduce requirement for high output power of the former source. In fact, the tripler based on unbalanced structure has been studied in our former research work, and the measured results show that the highest efficiency is 7.3% [8]. Compared with it, the performance of the 212 GHz tripler designed in this paper improves greatly.…”
Section: Ghz Triplermentioning
confidence: 68%
“…Compared with the doubler [8], its power capacity is smaller than this work, owing to the smaller number of anodes. Compared with the triplers in [12][13][14][15], the proposed tripler had higher output power and efficiency. Although a Because of the non-balanced circuit structure of the frequency multiplier, the efficiency is related to three variables: frequency, bias voltage, and input power.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the doubler [8], its power capacity is smaller than this work, owing to the smaller number of anodes. Compared with the triplers in [12][13][14][15], the proposed tripler had higher output power and efficiency. Although a high output power and broadband tripler work with monolithic HBV in [23], its efficiency is lower than in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the driving power was raised to 300 mW, the output power at 276 GHz reached a maximum of 15 mW. In 2020, Peter G. Hug-gard et al of ACST reported a 135-150 GHz tripler with low loss impedance matching based on waveguide resonator filter [97,98] . Impedance matching was achieved by adjusting the resonant frequency of the filter cavity, as shown in Fig.…”
Section: Balanced Frequency Doublersmentioning
confidence: 99%